Rapport and Relationship Building in a Therapeutic Community: Examining the Dynamic Between Correctional Officers and Incarcerated Persons. (February 2023) - Abdel-Salam, Sami; Antonio, Michael E.; Bratina, Michele P.; Kilmer, Ashley
Correctional officers (COs) are vital to prison safety. While focused on security, some believe COs should also be trained to engage in the rehabilitation of incarcerated persons by offering motivation and support. This study examined incarcerated persons' perceptions of COs working in a prison-based therapeutic community (TC). Data were gathered through qualitative interviews with individuals detained in a state correctional system for men. Findings revealed several themes related to incarcerated persons' perceptions of COs' knowledge toward treatment, their experiences and interactions with COs, and recommendations about how to improve the role of COs as therapeutic agents of change. Practical opportunities for implementing correctional research and practice using a positive criminology perspective are considered.